2018
DOI: 10.1159/000490809
|View full text |Cite
|
Sign up to set email alerts
|

Disorganization of the Retinal Inner Layers after Anti-VEGF Treatment for Macular Edema due to Branch Retinal Vein Occlusion

Abstract: Purpose: To evaluate the association between disorganization of the retinal inner layers (DRIL) and visual acuity (VA) after anti-VEGF treatment for macular edema (ME) due to branch retinal vein occlusion (BRVO). Methods: Sixty eyes of 60 patients were retrospectively investigated. Baseline characteristics and factors analyzed on optical coherence tomography (OCT) examination at the final visit were evaluated in association with VA at the final visit. Results: DRIL was detected in 39 eyes at the final visit. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
3
3
1
1
Order By: Relevance
“…Alternative or additional pathways may contribute to visual outcomes. Previous studies regarding visual outcomes have focused on the outer layers of the retina, such as the ELM, EZ, and IZ [15][16][17][18]20]. In contrast, there were no significant differences between the recurrence of macular edema and the incidences of ELM or EZ disruption in the current study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Alternative or additional pathways may contribute to visual outcomes. Previous studies regarding visual outcomes have focused on the outer layers of the retina, such as the ELM, EZ, and IZ [15][16][17][18]20]. In contrast, there were no significant differences between the recurrence of macular edema and the incidences of ELM or EZ disruption in the current study.…”
Section: Discussioncontrasting
confidence: 81%
“…A recent report stated that disorganization of the retinal inner layer (DRIL) may influence improvement of visual acuity in patients with central retinal vein occlusion (CRVO) or BRVO after 6 intravitreal injections of bevacizumab delivered monthly [19]. Conversely, 2 additional reports have shown that DRIL is not related to visual outcome in BRVO [20,21]. However, these prior studies did not assess recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the blockage of BRVO accounts for 65.52% in the supratemporal area and 34.48% in the infratemporal area. The obstruction was not found in the nasal side, which showed consistency with the proportion reported by Nakano E and Samara WA [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previously most studies focus on utilizing the loss of baseline indexes such as CMT, disorganization of the retinal inner layer (DRIL), subretinal fluid (SRF), hyperreflective foci (HF), external limiting membrane (ELM), ellipsoid zone (EZ), and interdigitation zone (IZ) to predict the long-term efficacy in RVO-ME (10,(17)(18)(19)(20)(21). However, due to blockade of retinal hemorrhage before treatment, large CMT, and poor ocular fixation due to poor visual function, the quality of the retinal interlayer structure obtained from OCT images is far from satisfactory.…”
Section: Discussionmentioning
confidence: 99%